2013
DOI: 10.1371/journal.pone.0067687
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Health Index (Phi) and Prostate Cancer Antigen 3 (PCA3) Significantly Improve Prostate Cancer Detection at Initial Biopsy in a Total PSA Range of 2–10 ng/ml

Abstract: Many efforts to reduce prostate specific antigen (PSA) overdiagnosis and overtreatment have been made. To this aim, Prostate Health Index (Phi) and Prostate Cancer Antigen 3 (PCA3) have been proposed as new more specific biomarkers. We evaluated the ability of phi and PCA3 to identify prostate cancer (PCa) at initial prostate biopsy in men with total PSA range of 2–10 ng/ml. The performance of phi and PCA3 were evaluated in 300 patients undergoing first prostate biopsy. ROC curve analyses tested the accuracy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
86
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 25 publications
0
86
0
2
Order By: Relevance
“…Within this range, more unnecessary biopsies can be spared compared with standard testing. These results have recently been supported by the DCA on a large ageindependent cohort with initial biopsies by Lazzeri et al [39] and Ferro et al [40].…”
mentioning
confidence: 57%
“…Within this range, more unnecessary biopsies can be spared compared with standard testing. These results have recently been supported by the DCA on a large ageindependent cohort with initial biopsies by Lazzeri et al [39] and Ferro et al [40].…”
mentioning
confidence: 57%
“…В ис-следованной выборке было 5 образцов в «серой зоне» ПСА они были корректно классифицированы при уста-новленных на предыдущем этапе ROC-анализа опти-мальных пороговых уровнях 1,86 и 1,48 для осадков и экзосом мочи соответственно (за исключением 1 ложноположительного случая при анализе экзосом). Это согласуется с тем, что PCA3 охарактеризован рядом авторов как маркер с диагностической точностью вы-ше, чем у общего и отношения свободного к общему ПСА, особенно в «серой зоне» 2-10 нг/мл [17,18], в том числе и при первичной диагностике РПЖ [19,20]. Вме-сте с тем необходимо иметь в виду малый объем выбор-ки и наличие «серой зоны» deltaCt, описанной нами ранее при анализе экспрессии РСА3 в РПЖ [16].…”
Section: сравнительный анализ экспрессии гена рса3: а -Roc-анализ эксunclassified
“…A similar study was performed by Catalona et al [17], which found that diagnosing using %fPSA had an AUC of 0.525, using fPSA had an AUC of 0.615, using p2PSA had an AUC of 0.557, 6 and using PHI had an AUC of 0.703 for 1,372 subjects. Additionally, Ferro et al [28] found that fPSA had an AUC of 0.60, %fPSA had an AUC of 0.62, %p2PSA had an AUC of 0.76, and PHI had an AUC of 0.77 for 300 subjects.…”
Section: A In-vitro Prostate Cancer Diagnostic Technologiesmentioning
confidence: 99%
“…A common urine-based biomarker is PCA3 (formerly DD3), a prostate specific non-coding RNA [29,30,32,36]. The reported studies [20,21,25,28,[37][38][39] showed an AUC ranging from 0.64-0.74 for PCA3. Hessel et al…”
Section: A In-vitro Prostate Cancer Diagnostic Technologiesmentioning
confidence: 99%
See 1 more Smart Citation